Space terahertz remote sensing technology - Hu, Weidong 1975-; Bai, Yuming 1989-; Lv, Xin (CRC Press, Taylor & Francis Group, 2024)
"This book examines terahertz technology and its applications in atmospheric remote sensing. Terahertz waves are electromagnetic radiation between microwaves and infrared radiation in the electromagnetic spectrum. They have the capability of greater directivity, higher power density, higher resolution imaging, richer fingerprint spectrum, wider bandwidth and faster transmission rate. Such properties promise great potential for terahertz technology applications in many fields, particularly in the detection of substances and the exploration of space. The book begins with an introduction to the development of space terahertz remote sensing and the underlying theories. The next seven chapters cover the key equipment and critical technologies for terahertz remote sensing, including the terahertz radiometer and its calibration and receiver link; the terahertz reflector antenna and its tolerance analysis; remote sensing imagery; and space resolution enhancement of both oversampled and non-oversampled data. The final chapter presents the application of terahertz imaging technology in the field of security inspection. This title will serve as a valuable reference for academics, students and engineers in the fields of terahertz technology, space science and remote sensing. Professionals in atmospheric remote sensing and inspection imaging will also benefit from this book"--
Includes bibliographical references. - Description based on print version record and CIP data provided by publisher
Keywords: Terahertz technology; Microwave remote sensing; Microwave detectors; Infrared imaging; Artificial satellites in remote sensing; Atmosphere -- Remote sensing; Electronic surveillance; Technologie térahertz; Télédétection hyperfréquence; Détecteurs à micro-ondes; Satellites artificiels en télédétection; Atmosphère; Télédétection; Surveillance électronique